Financial services and logistics innovation within agri-food value chains: A conceptual framework - Ambler, Kate; Bloem, Jeffrey R.; de Brauw, Alan (International Food Policy Research Institute, 2022)
Finance and logistics services for agricultural value chains based on technological innovations exist in several LMICs, but they are not often extended to small holders or SMEs working in the agricultural midstream. We consider the constraints to adoption of those services faced by smallholders or SMEs. Finance and logistics improvements hold promise for increased employment, but research is needed to understand where employment gains are most likely. All value chain innovations must carefully consider possible equity-efficiency tradeoffs to ensure change does not negatively affect poor and vulnerable populations.